2020
DOI: 10.1002/aisy.202000096
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Inspired Structural Plasticity through Reweighting and Rewiring in Multi‐Terminal Self‐Organizing Memristive Nanowire Networks

Abstract: Acting as artificial synapses, two‐terminal memristive devices are considered fundamental building blocks for the realization of artificial neural networks. Current memristive crossbar architectures demonstrate the implementation of neuromorphic computing paradigms, although they are unable to emulate typical features of biological neural networks such as high connectivity, adaptability through reconnection and rewiring, and long‐range spatio‐temporal correlation. Herein, self‐organizing memristive random nano… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 42 publications
2
114
2
Order By: Relevance
“…Atomic rearrangement present under the application of high voltage bias contributes to the rearrangement of grain boundaries responsible for the switching events. The observed mechanism is substantially different from what observed in random networks of nanowires where ionic transport is involved 14 , 15 , 17 , 18 , 55 . In our case the highly correlated re-arrangement of grain boundaries changes the local conductivity as observed in single metallic nanowires 56 .…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…Atomic rearrangement present under the application of high voltage bias contributes to the rearrangement of grain boundaries responsible for the switching events. The observed mechanism is substantially different from what observed in random networks of nanowires where ionic transport is involved 14 , 15 , 17 , 18 , 55 . In our case the highly correlated re-arrangement of grain boundaries changes the local conductivity as observed in single metallic nanowires 56 .…”
Section: Resultscontrasting
confidence: 76%
“…Random networks of metallic nanowires/nanoparticles in a polymeric matrix or passivated by shell of ligands or oxide layers have gained a renewed interest for the fabrication of non-linear circuital elements such as memristors and resistive switching devices for analog computing and neuromorphic data processing 14 18 . These systems are in the weak-coupling regime and their electrical behavior is determined by the formation/destruction of conducting junctions between isolated nanoparticles conferring neuromorphic properties to the networks 14 17 , 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This naturally produces a 2D spatial distribution of randomly oriented nanowires, interconnected by cross-point MIM junctions, with typical densities of 10 junctions/μm 2 and 0.5 nanowires/μm 2 [45,46]. Device electrodes can also be mask-deposited onto the substrate [47,48], thereby avoiding lithographic fabrication steps altogether. Metallic nanowires coated with either metal oxides or other electrolytes, such as Ag 2 S or PVP, result in NWN MIM junctions with resistive switching memory.…”
Section: Physical Mechanisms and Dynamicsmentioning
confidence: 99%
“…TiO 2 , NiO 2 ) [39] or, in the case of atomic switches, the chalcogenide electrolyte Ag 2 S, which undergoes a bias-catalysed transition to a metallic phase with a remarkably high diffusion coefficient for silver [45,54]. Studies have also found memristive switching in Ag-PVP nanowire systems [47,55]. This may be attributed to the amorphous phase of PVP, a polymer electrolyte, possessing more ion transport channels than a solid (i.e.…”
Section: Resistive Switching Memorymentioning
confidence: 99%
See 1 more Smart Citation